IDENTIFIKASI MISKONSEPSI SISWA PADA MATERI IPA KELAS VII SMPN 2 MARGA SEKAMPUNG - Sayuti Sri Lestari; Arwin Achmad; Rini Rita Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2017)
The research was aim to identify students misconceptions of science concept on seventh grade in second. Descriptive research. Samples were taken by simple random sampling that was 64 students. The quantitative data were from the test results of UN (2014-2015), pissa (2006) and TIMS (1999-2011). The qualitative data interviews of students' responses to science material of. The data analysis was conducted by CRI.The identification results misconceptions at 16, 76% 25 questions, 20 multiple choice and 5 reasoned essays. The results identification of students misconception was 26, 19% lower criteria. Material Science of the most common misconceptions ecosystem materi sub concept of interdependence between biotic components with highest. Percentage among other is 37.5% in the low criteria. It can be concluded that students who do not know the concept and had misconception was low criteria.Penelitian bertujuan mengidentifikasi miskonsepsi materi IPA semester genap pada siswa kelas VII. Penelitian deskriptif sederhana. Sampel diambil dengan simple Random Sampling jumlah 64 siswa. Data kuantitatif di peroleh dari hasil tes soal UN(2014-2015), PISSA (2006) dan TIMS (1999-2011). Data kualitatif dari wawancara tanggapan siswa terhadap materi IPA semester genap kelas VII. Analisis data dilakukan dengan metode CRI. Hasil identifikasi miskonsepsi yaitu 16,76% 25 soal, 20 pilihan jamak beralasan dan 5 esay. Hasil identifikasi miskonsepsi siswa 26,19% kriteria rendah. Materi IPA paling banyak terjadi miskonsepsi pada siswa ekosistem sub konsep saling ketergantungan antara komponen biotik. Persentase paling tinggi adalah 37,50% dalam kriteria rendah. Demikian dapat disimpulkan siswa yang tidak tahu konsep, mengalami miskonsepsi berkriteria rendah. Kata kunci: Certainly of Response Index (CRI), materi IPA, miskonsepsi